A research into the role of enterprise resource planning in financial decision making at Midlands State University - Masea, Yvonne Tsungai (Midlands State University, 2018)
The study was based on the challenge that arose in the reconciliation of student income in the finance section. The researcher found related literature on all the set objectives where the main research objective required the researcher to find out the effect of having two separate system manipulating accounting data and to assess if the introduction of an ERP would bring solutions to the challenges being faced by decision makers at Midlands State University. Questionnaires and interviews were used as the research instruments. The information obtained from the data collected was analyzed and presented by making use of simple tables, charts and graphs. From the research conducted the research findings indicate that there is an urgent need to educate employees and employ an ERP system as the variances were linked to system malfunctioning. The use of two separate information systems has a significant negative bearing on decision making as this was one of the research objectives of the study. The research study ultimately reflects that the implementation of ERP system was arguably chosen as the best practice of integration, through application integration.